Ramesses VI (KV9) Sarcophagus Conservation - Brock, Edwin C.
From the destruction of the sarcophagus in antiquity until its restoration beginning in the summer of 2001, the hundreds of fragments making up Ramesses VI’s inner sarcophagus remained scattered around the burial chamber of KV 9. Over the millennia they had been moved from the sarcophagus pit to the platforms at the north and south ends of the burial chamber. Project Director, Dr. Edwin Brock and his team’s goal was to finally reassemble the box and lid. This set, made of green conglomerate and mummiform in shape, is one of two sarcophagi found in the tomb. The other, outer sarcophagus was broken into two pieces and remains in the sarcophagus pit.